Social work and mental health - Golightley, Malcolm (LOS ANGELES SAGE, 2014)
While mental health is a core subject on the social work curriculum, many students find the breadth of the subject difficult to grasp. There is much to understand from law, policy and legislation, to ethical and value-based considerations. This book is written as an introduction to the complex issues around mental health. Law and policy are outlined whilst the author gives space to ethical considerations when working alongside the most vulnerable in society. There are clear links between policy, legislation and social work practice and learning features mean students can begin to think critically about a variety of mental health issues.
Contents note continued: Working together to safeguard children.
Previous edition: 2011.
Contents note continued: Working together to safeguard children.
Keywords: Psychiatric social work; Social psychiatry; Mental health; Social Work, Psychiatric; Mental Disorders; Mental Health; Psychiatric social work